2017
DOI: 10.26710/jbsee.v3i2.86
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the Major Leadership Theories in Comparison to the Competency Theory for Leadership Practice

Abstract: Purpose: This article presents perspectives on the review of eight major theories of leadership in comparison to the competency approach. Also, the definitions, significance, and benefits of the leadership competency concept are also highlighted. Methodology: A review of the various published literature on the major leadership theories, the competency theory, and the related topics on the scope of the study. Results: The findings of the review show the significance and relevance of the leadership c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 37 publications
0
24
0
6
Order By: Relevance
“…On the basis of many research studies/theories (Al Halbusi et al, 2018;. The lacking of leadership within the project performance had been seen one of the big problems for both industry & academia (Chow et al, 2017), and the same had been confirmed in numerous research studies (Ahmed & Anantatmula, 2017;Halbusi et al, 2018). Furthermore, the project manager ought to believe about the results that sustainability courses of action & controls may have an effect on the project.…”
Section: H1: Project Sustainability Is Positively Associated Construcmentioning
confidence: 97%
“…On the basis of many research studies/theories (Al Halbusi et al, 2018;. The lacking of leadership within the project performance had been seen one of the big problems for both industry & academia (Chow et al, 2017), and the same had been confirmed in numerous research studies (Ahmed & Anantatmula, 2017;Halbusi et al, 2018). Furthermore, the project manager ought to believe about the results that sustainability courses of action & controls may have an effect on the project.…”
Section: H1: Project Sustainability Is Positively Associated Construcmentioning
confidence: 97%
“…Merujuk pada Lussier dan Achua (2016), kepemimpinan merupakan sebuah isu utama dalam manajemen dan telah ada semenjak ratusan tahun lalu. Hal ini disebabkan peran kepemimpinan yang begitu penting untuk meningkatkan dan mencapai tujuan organisasi, politik, dan masyarakat (Chow, Salleh, & Ismail, 2017). Tujuan organisasi dapat dicapai apabila proses manajemen pada organisasi berjalan dengan baik.…”
Section: Pendahuluanunclassified
“…Teori kepemimpinan sifat (trait) merupakan teori kepemimpinan yang muncul pada akhir Perang Dunia Kedua (Bertocci, 2009). Pendekatan sifat ini hadir sebagaimana sebuah kemajuan yang berlanjut dari teori orang hebat (Chow et al, 2017) dimana terdapat perubahan fokus dari pemimpin terkemuka yang terkenal menuju pada kepemilikan sifat-sifat kepemimpinan (Clark & Harrison, 2018). Namun, meskipun kepemimpinan telah menjadi topik kajian beberapa ratus tahun silam, tetapi penelitian empiris yang dilakukan secara sistematis tidak benar-benar dimulai sampai pada tahun 1930an dan 1940-an (Bass & Bass, 2008;Bolden et al, 2011;Lussier & Achua, 2010).…”
Section: Teori Kepemimpinan "Trait"unclassified
See 1 more Smart Citation
“…Additionally, other common citizens can be and are also involved in genocide as Milgram (1960:6) observes that -ordinary people, simply doing their jobs, without any particular hostility on their part, can become agents in a terrible destructive process‖. Many of the Nigerian state authorities are not living up to their leadership responsibilities which entails responses to changes (Chow, Salleh & Ismail, 2017).…”
Section: The Perpetrators In Actionmentioning
confidence: 99%